2018
DOI: 10.1007/s41348-018-0162-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of laminarin and calcium oxide for the control of grape powdery mildew on Vitis vinifera cv. Moscato

Abstract: Erysiphe necator is favorably influenced by the increase in temperatures and remains the main pathogen threatening grape in Northern Italy. In the present work the efficacy of laminarin and calcium oxide in the control of grape powdery mildew was evaluated, comparing them to sulphur.Two tests were carried out on potted grape "Moscato" plants in 2017 and two field trials were carried out in Italy during 2016 and 2017 on a vineyard of the "Moscato" variety. Laminarin and calcium oxide showed, for the first time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 19 publications
5
37
0
Order By: Relevance
“…Microbial functional diversity was also inspected by means of the Biolog EcoPlate TM technique. Integration of these data with disease indices revealed that, besides an evident genotype effect, AcS-Mt, K-Pho, and Lam successfully acted against powdery mildew spread, consistent with the previous observations [18,24,79]. Since our experimental set-up was based on an environmentally friendly protocol, these findings confirmed the effectiveness of the tested products and opened the venue for their employment in disease management programs in viticulture.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Microbial functional diversity was also inspected by means of the Biolog EcoPlate TM technique. Integration of these data with disease indices revealed that, besides an evident genotype effect, AcS-Mt, K-Pho, and Lam successfully acted against powdery mildew spread, consistent with the previous observations [18,24,79]. Since our experimental set-up was based on an environmentally friendly protocol, these findings confirmed the effectiveness of the tested products and opened the venue for their employment in disease management programs in viticulture.…”
Section: Discussionsupporting
confidence: 88%
“…In response to the ongoing global climate change, and considering the increasing need to adopt environmentally friendly pesticides, many products have been tested to reduce the massive chemical inputs applied against grape pathogens [78]. Here, we observed, as previously demonstrated by other works [18,21,23], that plant elicitors could be adopted as alternative strategies to effectively control powdery mildew.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…58% of clusters in the untreated control (CTRL) were affected by U. necator , all other treatments reduced the levels of powdery mildew infection and no symptoms associated to downy mildew were observed [ 22 ]. Lam and K-Pho were among the treatments showing the best control of the pathogen, followed by Fos-Al and Met, while EOW induced a very limited control of powdery mildew [ 22 , 27 ]. In the vineyard where the experiments were conducted, the vintage 2017 was characterized by low rainfall ( Figure S1 ), especially in the summer months (July and August), thus inducing limited development of oomycete-associated diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Rantsiou et al [ 22 ] has already verified the impact of these compounds (e.g., laminarin and chito-oligosaccharides) on yield and vine vigor, skin features (including phenolic composition) and yeast community present on grape berries at harvest. Particularly, laminarin, which is extracted from the brown algae Laminaria digitate , is already known to act inducing resistance against downy and powdery mildew and grey mould in grapevine [ 23 , 24 , 25 , 26 , 27 ]. At molecular level, although berry transcriptomic profiles have been already studied with the aim to identify the candidate genes associated with phenotypic plasticity [ 6 ] and to developmental processes such as ripening [ 28 ] also in ‘Nebbiolo’ grape [ 10 ], few information are present on the changes associated to the application of biocontrol products.…”
Section: Introductionmentioning
confidence: 99%